2003
DOI: 10.1038/nature01750
|View full text |Cite
|
Sign up to set email alerts
|

A very energetic supernova associated with the γ-ray burst of 29 March 2003

Abstract: Over the past five years evidence has mounted that long-duration (> 2 s) γ-ray bursts (GRBs) the most brilliant of all astronomical explosionssignal the collapse of massive stars in our Universe. This evidence was originally based on the probable association of one unusual GRB with a supernova 1 , but now includes the association of GRBs with regions of massive star formation in distant galaxies 2,3 , the appearance of supernova-like 'bumps' in the optical afterglow light curves of several bursts 4-6 and lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
1,299
3
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,436 publications
(1,351 citation statements)
references
References 25 publications
44
1,299
3
5
Order By: Relevance
“…These are known as 'broad-line SNe Ic' (or SNe Ic BL), and a further subset of SNe Ic BL have been linked to long duration Gamma Ray Bursts (LGRBs, see e.g. Galama et al 1998;Hjorth et al 2003). From a theoretical viewpoint, historically SN progenitors have been separated into two classes.…”
Section: Introductionmentioning
confidence: 99%
“…These are known as 'broad-line SNe Ic' (or SNe Ic BL), and a further subset of SNe Ic BL have been linked to long duration Gamma Ray Bursts (LGRBs, see e.g. Galama et al 1998;Hjorth et al 2003). From a theoretical viewpoint, historically SN progenitors have been separated into two classes.…”
Section: Introductionmentioning
confidence: 99%
“…LGRBs have been associated to supernovae (Galama et al 1999;Stanek et al 2003;Hjorth et al 2003;Matheson et al 2003), all of which lacked any hydrogen or helium lines and so were of the type-Ib/c (e.g., Filippenko 1997). In combination with the fact that any outer hydrogen layer of the star would stop the LGRB escaping (MacFadyen & Woosley 1999), means that the hydrogen envelope of the progenitor has to be lost before it undergoes gravitational collapse.…”
Section: Manymentioning
confidence: 99%
“…The association of LGRBs with the death of massive stars (Galama et al 1999;Stanek et al 2003;Hjorth et al 2003;Matheson et al 2003) facilitates their use as star formation tracers and their naturally luminous nature would complement or even surpass conventional methods at high redshift. However, before this connection can be used routinely and robustly, the way in which they trace one another must be known accurately.…”
Section: Manymentioning
confidence: 99%
“…Several observational evidences point toward this hypothesis. At low redshift, the association between the GRBs and massive star progenitors is well established by (i) Type Ic supernovae (SNe) identified at the positions of GRB events (Hjorth et al 2003;Mirabal et al 2006) and (ii) the location of GRBs in Wolf-Rayet galaxies (Hammer et al 2006). At high redshift, the connection between GRBs and star-forming regions is inferred by (i) GRBs found in blue galaxies with nebular lines indicative of on-going star formation (Le Floc'h et al 2003;Prochaska et al 2004) and (ii) GRBs observed within a few kpc from the weighted flux centroid of their host (Fruchter et al 2006).…”
Section: Introductionmentioning
confidence: 99%